"Issue" Management of Da'wah Strategy and Use of Information Technology - Sofyan Hadi (Jurnal Al-Hikmah, 2023)
Islam is a religion full of mercy not only for its adherents but also for the entire universe (Ar-Rahmatan Lil 'Alamien). The digital era and globalization demand its followers to constantly adapt in order not to be left behind amidst the tremendous development of information and technology. Hence, there is a need for proper filtering and management in understanding the noble mission of da'wah. The aim of this research is to explore 1) management issues, 2) issues in management and their relationship with the reputation of da'is/organizations/companies, and 3) the steps for controlling and managing these issues. In this study, the research method employed is library research involving the utilization of library resources and literature to gather relevant data on the research topic. Researchers used library catalogs and online databases to search for and select high-quality sources. The findings of this research indicate that among the main management issues for implementing classical to modern da'wah strategies and the use of Information Technology include: issue management, steps for controlling and managing issues, the function of issue management (intelligent planning and operations, strong defense and smart attacks, exploring foundations). Additionally, the issue management process model by Chase & Jones comprises five models: issue identification, issue analysis, choice of change strategy for the issue, Action Programming against the Issue, and evaluation of outcomes.